Non-operative management of ulnar collateral ligament injuries in the throwing athlete - Smucny, M.; Westermann, R. W.; Winters, M.; Schickendantz, M. S. (The Physician and Sportsmedicine, 2017)
Medial ulnar collateral ligament (UCL) injuries have become increasingly prevalent in overhead athletes. The orthopaedic literature contains a wealth of information on operative management of these injuries. However, there are few high-quality longitudinal studies on non-operative care of UCL injuries. The purpose of this review is to describe the non-operative approach to managing UCL injuries, including recommended rehabilitation strategies and predictors of successful non-operative treatment.